A Carbon Fee as Mitigation for Fossil Fuel Extraction on Federal Lands - Burger, Michael (Columbia Journal of Environmental Law, 2019)
Since the enactment of the Mineral Leasing Act in 1920 and the Outer Continental Shelf Lands Act in 1953 the United States federal government has leased onshore and submerged public lands to private companies to mine coal and drill for oil and gas, often at a steep discount, and often with little or no accounting for the broad scope of these fossil fuels’ environmental externalities. The raft of environmental legislation that passed through Congress in the 1970s addressed these issues to some degree. For example, the Federal Coal Leasing Amendment Act required the United States to, among other things, recover “fair market value” of each lease; the Surface Mine Control and Reclamation Act established a system for controlling local environmental impacts from coal mining; the National Environmental Policy Act required the federal government to assess, analyze and disclose potential adverse environmental impacts from federal actions, including cumulative and indirect effects; the Federal Land Policy and Management Act and the National Forest Management Act imposed multiple use and sustainability requirements on public lands management; and the Clean Air Act and the Clean Water Act addressed aspects of air quality and water pollution by imposing new permit requirements on extractive operations. To date, however, the federal fossil fuel leasing programs have not adequately addressed the upstream and downstream impacts of federal leases—air pollution associated with the extraction, transportation and combustion of fossil fuels that contributes significantly to smog, acid rain and, most importantly here, climate change. This Article develops an argument for using a mitigation-based rationale to deliver a climate change impacts fee on coal, oil, and gas extracted from federal lands. Assuming that new federal leases for coal, oil, and gas will be issued and that existing leases will be renewed, Interior has the legal obligation to mitigate, as well as the legal authority to seek compensation for, the adverse environmental, social, and public health impacts attributable to the resulting GHG emissions—and it makes policy sense to do so. Pursuant to NEPA and its implementing regulations, upstream GHG emissions—emissions from the extraction of fossil fuels from federal lands—are direct effects of a lease; downstream GHG emissions—emissions from the transportation and combustion of the fossil fuel—are indirect effects. The climate change impacts attributable to those upstream and downstream emissions, then, are unavoidable (or “residual”) impacts from leasing programs that involve the issuance of new leases or renewal of existing ones; therefore, they are properly the subject of compensatory mitigation, such as a climate change impacts fee. As a matter of the government’s property ownership and regulatory design, this climate change impacts fee could come as part of the bonus bid on a lease, as an in-lieu fee, as part of the regulatory rental fee, as a stand-alone lease condition, as part of the royalty calculation, or in some other form. As a matter of environmental review, a climate change impacts fee could serve as an element of one of the alternatives being analyzed. However, it may be even more useful to analyze the concept as an independent alternative—that is, as an element of program design, or as an adder or overlay to all of the other alternatives.